A Case of Sarcoidosis in a Forensic Setting – What Has Been Found as Cause of Death - Davceva N; Krsteska, B; Popova G (Institute of Experimental Morphology, Pathology and Anthropology with Museum Bulgarian Anatomical Society, 2025)
Sarcoidosis is a multisystem inflammatory disease of unknown etiology with a particular clinical and pathological picture. Pathologically can be confirmed with the finding of non- caseating (non-necrotizing) granulomas containing epithelioid cells and large multinucleated giant cells. Sarcoidosis is associated with an increased risk of premature death; it is twice as high as the general population. The common cause of death includes: cardiac failure due to cardiac sarcoidosis, lung disease associated with pulmonal hypertension, infection etc. In this case presentation we show finding of another and not so common cause of cardiac death in a patient with sarcoidosis i.e. bacterial myocarditis represented by clusters of bacterial colonies throughout the myocardial tissue.
Keywords: sarcoidosis; cardiac sarcoidosis; bacterial myocarditis